2019
DOI: 10.1016/j.jhazmat.2018.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Determining the long-term operational performance of pump and treat and the possibility of closure for a large TCE plume

Abstract: The purpose of this study is to evaluate the impact of heterogeneity on the long-term performance of a large pump-and-treat (PAT) system that has been in operation for 30 years at a site located in Tucson, AZ. A 3D numerical model was developed. Three different concentrations were examined: composite concentration in the influent to the treatment plant, resident concentration in the aquifer, and concentration for downgradient boundary discharge. The time scales needed for concentrations measured in these ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…2013; Seyedabbasi et al 2013; Guo et al 2019). Several publications have indicated that PAT in settings with back diffusion may require timeframes on the order of one or more centuries for restoration (LaBolle and Fogg 2001; Lemming et al 2012; McDade et al 2013; Guo et al 2019). For example, LaBolle and Fogg (2001) simulated PAT remediation using the alluvial aquifer characteristics found at the Lawrence Livermore National Laboratory Superfund Site in Livermore, California.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2013; Seyedabbasi et al 2013; Guo et al 2019). Several publications have indicated that PAT in settings with back diffusion may require timeframes on the order of one or more centuries for restoration (LaBolle and Fogg 2001; Lemming et al 2012; McDade et al 2013; Guo et al 2019). For example, LaBolle and Fogg (2001) simulated PAT remediation using the alluvial aquifer characteristics found at the Lawrence Livermore National Laboratory Superfund Site in Livermore, California.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Non-aqueous phase liquids (NAPLs), such as petroleum hydrocarbons and chlorinated solvents, are among the most widespread (and consequential) soil and groundwater contaminants, and they are increasingly being recognized as serious environmental problems [1][2][3]. These water-immiscible organic liquids are classified into light NAPL (LNAPL) and dense NAPL (DNAPL) based on their densities [4].…”
Section: Introductionmentioning
confidence: 99%
“…When combined with particle tracking software (Pollock, 2012), models can provide estimates of subsurface travel time and flow path depth, parameters that can be highly influential to discharge temperature and chemistry (Briggs et al, 2018; Winter et al, 1998). Although at small spatial scales (10 0 –10 2 km 2 ) simulated groundwater discharge and flow path characteristics have been examined (e.g., Carniato et al, 2015; Guo et al, 2019; Kaandorp et al, 2018; Mo et al, 2017), many studies in mid‐ to large‐sized watersheds (>10 2 km 2 ) do not examine these patterns (e.g., Feinstein et al, 2010; Masterson et al, 2016; Parsen et al, 2016; Reeve et al, 2001; Sanford et al, 2012).…”
Section: Introductionmentioning
confidence: 99%